Design-to-Test Approach for Programmable Controllers in Safety-Critical Automation Systems - Ma, Canlong; Provost, Julien (IEEE transactions on industrial informatics, 2020)
This article presents a design-to-test (DTT) approach for enhancing black-box complete conformance testing of programmable controllers, where their specifications can be modeled as finite state machines. Given an automation system, the testing objective is to check whether its implemented controllers conform to the expected behavior with regard to the specification models. The DTT approach analyzes the specification models and, if necessary, automatically modifies them at the cost of limited design overhead, so that the testability of the final implemented controllers can be ensured/improved. By design, this approach also guarantees that the behavior of implemented controllers remains unchanged during normal execution (i.e., when not connected to a test bench).